Intensity-Modulated Radiation Therapy for Rectal Carcinoma Can Reduce Treatment Breaks and Emergency Department Visits. (12th August 2012) - Jabbour, Salma K.; Patel, Shyamal; Herman, Joseph M.; Wild, Aaron; Nagda, Suneel N.; Altoos, Taghrid; Tunceroglu, Ahmet; Azad, Nilofer; Gearheart, Susan; Moss, Rebecca A.; Poplin, Elizabeth; Levinson, Lydia L.; et al.
Abstract : Purpose . To compare the acute toxicities of IMRT to 3D-conformal radiation therapy (3DCRT) in the treatment of rectal cancer. Methods and Materials . Eighty-six patients with rectal cancer preoperatively treated with IMRT (n = 30 ) and 3DCRT (n = 56 ) were retrospectively reviewed. Rates of acute toxicity between IMRT and 3DCRT were compared for anorexia, dehydration, diarrhea, nausea, vomiting, weight loss, radiation dermatitis, fatigue, pain, urinary frequency, and blood counts. Fisher's exact test and chi-square analysis were applied to detect statistical differences in incidences of toxicity between these two groups of patients. Results . There were fewer hospitalizations and emergency department visits in the group treated with IMRT compared with 3DCRT (P = 0.005 ) and no treatment breaks with IMRT compared to 20% with 3DCRT (P = 0.0002 ). Patients treated with IMRT had a significant reduction in grade ≥3 toxicities versus grade ≤2 toxicities (P = 0.016 ) when compared to 3DCRT. The incidence of grade ≥3 diarrhea was 9% among 3DCRT patients compared to 3% among IMRT patients (P = 0.31 ). Conclusions . IMRT for rectal cancer can reduce treatment breaks, emergency department visits, hospitalizations, and all grade ≥3 toxicities compared to 3DCRT. Further evaluation and followup is warranted to determine late toxicities and long-term results of IMRT.